Media Sosial Youtube Sebagai Sarana Personal Branding Dedi Mulyadi - Rosadi, Siti Fatimah Srihardiyanti; Yulyana, Eka; Nababan, Rudyk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Social media is currently used by a number of politicians and public officials with the aim of increasing public trust and forming a good image of it. Personal branding is carried out by a number of politicians or officials to make it easier for them to carry out political communication with the community. Dedi Mulyadi is a politician and a state official who is very active on Youtube social media in shaping his personal branding. This article describes the formation of personal branding carried out by Dedi Mulyadi through four strategies for the formation of personal branding, namely determine who you are, determine what you do, position yourself and manage your brand. The study used a descriptive qualitative approach with results showing that Dedi Mulyadi succeeded in forming a self-image through four personal branding strategies that made him a politician who was close to the community and was elected as an official in the DPR RI.